A157 THE EFFECTIVENESS OF A STANDARDIZED BIOLOGIC CARE PATHWAY IN THE MANAGEMENT AND TREATMENT OF INFLAMMATORY BOWEL DISEASE. (26th February 2020) - Willett, N; Heisler, C; Nazer, N; Currie, B; Phalen-Kelly, K; Stewart, M; Jones, J
Abstract: Background: Inflammatory Bowel Disease (IBD) is a class of chronic immune-mediated diseases. Biologics have revolutionized the treatment of IBD. Existing literature suggests significant variation exists in the use of biologic treatment among physicians, from provider-specific prescribing to completion of the pre-biologic workup. These differences may influence the effectiveness of achieving and maintaining long-term remission. Clinical care pathways may serve to standardize the use of biologics in the treatment of IBD leading to improvements in patient outcomes and consistency of care provided from different specialists. Aims: To determine if the use of biologics to treat IBD managed within a standardized biologic care pathway (BCP) is safer and more effective compared to the current standard of care. Methods: This was a retrospective, real-world cohort study of a prospectively implemented evidence-based BCP at the Nova Scotia Collaborative IBD (NSCIBD) program between 2015 and 2019. Patient inclusion criteria consisted of any adult with a diagnosis of IBD (including Crohn's Disease, ulcerative colitis, IBD-Unclassified) aged 18 years or older who was managed within the NSCIBD program. Preliminary descriptive analyses of the data are presented. Data collection is ongoing and multivariate analyses will be presented in full at CDDW. Results: In total 249 patients were included in the cohort study (111 BCP patients, 138 non-BCP patients). The mean age was 49 years (range of 17–86 years). Sixty-nine percent (171/249) of patients were diagnosed with CD, 28% (70/249) with UC, and 3% (8/249) with IBD-U. The mean duration of disease was 13 years (range of 0–36 years). Use of combination therapy was similar between the cohorts with 64% of BCP patients (n=102) and 63% of non-BCP patients (n=123) on combination therapy. Thirty-eight percent of the BCP cohort required dosing interval changes vs. 29% in the non-BCP cohort (0.24 fold higher in BCP cohort). Seventy-one percent of the BCP patients were exposed to TDM vs. 41% of the non-BCP cohort (0.40-fold more TDM in pathway cohort). Although 34% of BCP patients and 38% of non-BCP cohort patients reached clinical remission (n=103 and 125, respectively), 38% of BCP patients and 21% of non-BCP patients achieved endoscopic remission (0.5-fold lower in the non-BCP cohort), (n=29 and 53, respectively). Conclusions: Preliminary analyses suggest patients managed within a BCP have their biologic management guided more often by the results of TDM and objective biomarkers than those not managed within a BCP. Although clinical remission was observed to be similar between the cohorts, attainment of endoscopic remission was more likely amongst patients managed within the BCP. Additional multivariate analyses will be presented at CDDW with a larger cohort size. Funding Agencies: None